HOW TOP MANAGEMENT TEAMDIVERSITY INFLUENCES COMPANY PERFORMANCE?: THE CASE OF INDONESIAN STATE-OWNED ENTERPRISES HOLDING - Permana, Erwin; Sri Widyastuti; Achsanul Qosasi (Dinasti Publisher, 2020)
The research conducted at SOEs Holding aims to analyze the effect of TMT diversity on company performance. The research samples are forty Indonesian SOEs that incorporated into four SOEs Holding that surveyed through the questionnaire. The data analysis technique uses Structural Equation Model (SEM) with SmartPLS. The results concluded that TMT diversity had a significant effect on corporate culture, which mediates TMT diversity’s significant effect on company performance. Nevertheless, without corporate culture as the mediating variable, TMT diversity has no significant effect on company performance.